Clinical experience of switching patients with severe hemophilia to rVIII-SingleChain or rIX-FP. (1st February 2023) - Oldenburg, Johannes; Pipe, Steven W.; Mancuso, Maria Elisa; Klamroth, Robert; Hassoun, Abel; Olivieri, Martin; Goldmann, Georg; Kenet, Gili; Miesbach, Wolfgang; Schmiedl, Jolana; Hegemann, Inga
Abstract: Objective: Prophylaxis treatment is the current standard of care for patients with severe hemophilia. Factor concentrates with improved pharmacokinetics have offered more options for individualizing treatment. The treatment focus may be on increased protection, aiming for higher trough factor levels or longer dosing intervals to reduce the burden of hemophilia. Both aspects can have long-term effects on joint health. Products, such as rVIII‑SingleChain and rIX-FP have been developed to reduce the treatment burden for patients with hemophilia and optimize prophylactic efficacy. The objective of this report is to provide a summary of the clinical experience of different Hemophilia Treatment Centers in managing the switch to rVIII-SingleChain or rIX-FP in patients with hemophilia. Methods: This report summarizes a selection of patient cases presented at the 3rd Alliance for Coagulation Academy Meeting in October 2020. The cases from the participating centers provide examples of the clinical experience in managing patients' switch to rVIII-SingleChain and rIX‑FP, including which types of patients are suitable for switching, and practical steps in managing a switch. Results: It is important to take into consideration the physical and social fulfillment of the patient when deciding to switch to rVIII-SingleChain or rIX-FP. The physician plays an important role in the motivation of patients as they understand not only the patient's needs but the potential benefits of the new treatment. Conclusion: The selected patient cases reported here demonstrate that patients may wish to switch factor products for a variety of reasons; therefore, it is critical to understand why patients switch and what they expect from switching.